Weather Shocks and Urban Livelihood Strategies: The Gender Dimension of Household Vulnerability in the Kumi District Of Uganda - Akampumuza, Precious; Matsuda, Hirotaka (The Journal of Development Studies, 2017)
The Teso sub-region of Uganda suffered numerous weather shocks in the past, with devastating food security consequences. Using household fixed effects and propensity score matching methods, we analyse the impact of exposure to drought, flood and severe incidence of pests and diseases on household consumption expenditure per adult equivalent for a random sample of households from Kumi Town Council. We find that weather shocks reduce consumption by 17 per cent and that the consumption decline is significantly larger among female-headed households. We also find a higher likelihood of non-farm employment, borrowing and receiving remittances in order to cope with the shocks.
Keywords: Household Vulnerability; Gender Dimension; Weather Shocks; Urban Livelihood